Minimally invasive salvage lymphadenectomy in gynecological cancer patients: A single institution series. Issue 10 (October 2018) - Gallotta, Valerio; Giudice, Maria Teresa; Conte, Carmine; Sarandeses, Alicia Vazquez; D'Indinosante, Marco; Federico, Alex; Tortorella, Lucia; Carbone, Maria Vittoria; Gueli Alletti, Salvatore; Vizzielli, Giuseppe; Costantini, Barbara; Scambia, Giovanni; et al.
Abstract: Background: to assess the feasibility of minimally invasive surgery in the management of lymph-nodal recurrences of gynecological cancers, in terms of surgical and oncological outcomes. Methods: we retrospectively collected patients with isolated lymph-nodal recurrent disease of gynecological malignancies who underwent to minimally invasive lymphadenectomy at Catholic University of the Sacred Hearth in Rome (Italy), from January 2013 to November 2017. Results: Forty patients were considered eligible (31 LPS, 9 Robot); 24 (60.0%) with an ovarian cancer, 8 (20.0%) with a cervical cancer and 8 (20.0%) with an endometrial cancer recurrence. The most frequent site of lymph-nodal recurrence was represented by the aortic region (47.5%), while 18 patients (45.0%) experiencing pelvic lymph-nodal recurrence, 2 (5.0%) both pelvic and aortic relapse, and only 1 (2.5%) had an hepato-celiac lymph node recurrence. No patient required a laparotomic conversion. Median operative time was 220 min, median EBL was 80 mL, and median post-operative hospital stay was 2 days. There were 2 (5.0%) intra-operative and 4 (10.0%) post-operative complications, of which 2 were grade 3. The median follow-up was 22.5 months, and during this time 15 patients showed another relapse with a median time to progression of 12 months. Seven women died because of the disease. The 2-year post-relapse disease-free survival (PR-DFS) was 54.7%, and the 2-year post-relapse overall survival (PR-OS) was 79.3%. Conclusions: In our experience minimally invasive surgery is a valid therapeutic approach in very select patients with localized lymph-nodal recurrence of gynecological cancers, with benefits about peri and post-operative morbidities and without compromising their oncological outcome.